Azole-resistant Aspergillus fumigatus in Denmark: a laboratory-based study on resistance mechanisms and genotypes. (June 2016) - Jensen, R.H.; Hagen, F.; Astvad, K.M.T.; Tyron, A.; Meis, J.F.; Arendrup, M.C.
Abstract: Azole-resistant Aspergillus fumigatus originating from the environment as well as induced during therapy are continuously emerging in Danish clinical settings. We performed a laboratory-based retrospective study (2010–2014) of azole resistance and genetic relationship of A. fumigatus at the national mycology reference laboratory of Denmark. A total of 1162 clinical and 133 environmental A. fumigatus isolates were identified by morphology, thermotolerance and/or β-tubulin sequencing. Screening for azole resistance was carried out using azole agar, and resistant isolates were susceptibility tested by the EUCAST (European Committee on Antimicrobial Susceptibility Testing) E.Def 9.2 reference method and CYP51A sequenced. Genotyping was performed for outbreak investigation and, when appropriate, short tandem repeat Aspergillus fumigatus microsatellite assay. All 133 environmental A. fumigatus isolates were azole susceptible. However, from 2010 to 2014, there was an increasing prevalence of azole resistance (from 1.4 to 6% isolates (p <0.001) and 1.8 to 4% patients (p <0.05)) among the clinical isolates, with the well-known environmental CYP51A variant TR34 /L98H responsible for >50% of the azole resistance mechanisms. Among 184 Danish A. fumigatus isolates, 120 unique genotypes were identified and compared to a collection of 1822 international genotypes. Seven (5.8%) Danish genotypes were shared between isolates within Denmark but with different origin, 19 (15.8%) were shared with foreign genotypes, and two (11.8%) of 17 genotypes of isolates carrying the TR34 /L98H resistance mechanisms were identical to two Dutch TR34 /L98H isolates. Our findings underlines the demand for correct identification and susceptibility testing of clinical mould isolates. Furthermore, although complex, genotyping supported the hypotheses regarding clonal expansion and the potential of a single origin for the TR34 /L98H clone.